Scale-up challenges in the production of nanomedicines from lab to industry - Tagit, Oya (Henry Stewart Talks, 2023)
Batch vs. continuous processing, Manufacturing, Nanocarrier, Nanomaterial, Nanoscale therapeutics, Particle size, Scaling up